2018
DOI: 10.1007/s12178-018-9508-x
|View full text |Cite
|
Sign up to set email alerts
|

Special Considerations in the Management of Diabetic Ankle Fractures

Abstract: Non-operative management of unstable ankle fractures in patients with diabetes results in an unacceptably high rate of complications. Operatively managed patients with uncomplicated diabetes seem to fair as well as patients without diabetes. Thus, it is important to recognize patients as either complicated or uncomplicated at the onset of their treatment based on comorbidities. There is limited evidence to guide the management of ankle fractures in patients with diabetes, in particular those deemed complicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…According to the International Diabetes Federation (IDF), the global prevalence of DM in 2011 was 366 million, but it is estimated that in 2030 DM will affect 552 million of people 9,10 . Therefore, it is reported ankle/tibial plafond fractures and diabetes mellitus are both increasing in prevalence 7 . Patients with both diabetes and an ankle fracture have been shown to have an increased rate of complications which can be catastrophic 7 .…”
Section: Patient Comorbiditiesmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the International Diabetes Federation (IDF), the global prevalence of DM in 2011 was 366 million, but it is estimated that in 2030 DM will affect 552 million of people 9,10 . Therefore, it is reported ankle/tibial plafond fractures and diabetes mellitus are both increasing in prevalence 7 . Patients with both diabetes and an ankle fracture have been shown to have an increased rate of complications which can be catastrophic 7 .…”
Section: Patient Comorbiditiesmentioning
confidence: 99%
“…Therefore, it is reported ankle/tibial plafond fractures and diabetes mellitus are both increasing in prevalence 7 . Patients with both diabetes and an ankle fracture have been shown to have an increased rate of complications which can be catastrophic 7 . It is reported that medical expenses for diabetic patients are over two times higher than nondiabetics and the total cost of DM management was about $ 245 billion dollars in 2012 in the USA 11 .…”
Section: Patient Comorbiditiesmentioning
confidence: 99%
See 3 more Smart Citations